2016
DOI: 10.1638/2015-0146.1
|View full text |Cite
|
Sign up to set email alerts
|

COMBINATION THERAPY WITH FLUOXETINE AND ALPRAZOLAM TO CONTROL ANXIETY IN A HAND-REARED SNOW LEOPARD (UNCIA UNCIA)

Abstract: A captive hand-reared adult male snow leopard ( Uncia uncia ) was treated for anxiety associated with taunting from visitors, the presence of large crowds, and introduction to a female for breeding. Behaviors included shaking, chewing on tail, panting, panicking, and bouncing off the viewing glass, pacing, and avoidance of the female. Combination therapy of oral fluoxetine and alprazolam were administered initially to minimize anxious behaviors while the fluoxetine achieved therapeutic levels. The alprazolam w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Despite their reported efficacy in other species (Poulsen et al 1996;Baker 2002;Hugo et al 2003;Seibert 2007;Yalcin and Aytug 2007;Landsberg et al 2008;Holman 2016;Kaur et al 2016), this survey suggested a very low use of SSRIs, with only 8.2% (4/49) of respondent veterinarians suggesting use of these agents for behavioural issues in ridden horses. Whereas acepromazine and reserpine were suggested far more commonly, 57.1% (28/49) and 44.9% (22/49), respectively.…”
Section: Ssris To Treat Behaviour Issues In Horsesmentioning
confidence: 67%
See 2 more Smart Citations
“…Despite their reported efficacy in other species (Poulsen et al 1996;Baker 2002;Hugo et al 2003;Seibert 2007;Yalcin and Aytug 2007;Landsberg et al 2008;Holman 2016;Kaur et al 2016), this survey suggested a very low use of SSRIs, with only 8.2% (4/49) of respondent veterinarians suggesting use of these agents for behavioural issues in ridden horses. Whereas acepromazine and reserpine were suggested far more commonly, 57.1% (28/49) and 44.9% (22/49), respectively.…”
Section: Ssris To Treat Behaviour Issues In Horsesmentioning
confidence: 67%
“…More extensive use of SSRIs in horses may be a potential option to address owner/rider needs and improve horse welfare. SSRIs have been successfully used in other species to address behaviours such as anxiety (Landsberg et al 2008;Pineda et al 2014;Karagiannis et al 2015;Holman 2016), aggression (Seksel 2008) and compulsive disorders (Bowen and Heath 2005;Ogata et al 2013), and have previously demonstrated positive results in the treatment of stereotypic behaviours in horses (Nurnberg et al 1997) and other species (Poulsen et al 1996;Vogel and Stein 2000;Hugo et al 2003;Yalcin and Aytug 2007;Holman 2016).…”
Section: Ssris To Treat Behaviour Issues In Horsesmentioning
confidence: 99%
See 1 more Smart Citation